Pengelolaan Kualitas Air Terhadap Tingkat Kelangsungan Hidup Udang Vaname (Litopenaeus Vannamei) di PT. Benur Top De Heus Askra - Haspiani Haspiani; Megawati Megawati; Akmal Abdullah (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2024)
This water quality is very important to ensure a healthy shrimp life period. Water quality for this activity is influenced by several water quality parameters including, temperatur, Ph, salinity and alkalinity parameters. The aim of this research on water quality management is to find out how water quality management affects the survival rate in rearing vaname shrimp larvae (Litopenaeus vannamei) at PT.Benur Top De Heus Askra. The data analysis method in this research uses quantitative descriptive analysis techniques. The results show that water quality management at PT.Benur Top De Heus Askra increase the survival rate of vaname shrimp, the survival rate of vaname shrimp at PT.Benur Top De Heus Askra above 80%, this is achieved by maintaining water quality management.